IMPLEMENTATION OF SEM-PLS MODELING ON THE IMPACT OF THE REGIONAL COMPETITIVENESS INDEX ON SOCIOECONOMIC MACRO VARIABLES - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Dyah Purwanti; Sigit Budiantono (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The Regional Competitiveness Index (RCI) is one of the essential indicators to measure the ability of a region to compete with other regions in the economic, social, and environmental fields. Increasing regional competitiveness is one of the goals desired by every local government to encourage economic growth and community welfare. This study aims of the research to find out the relationship between the Regional Competitiveness Index (RCI) and socioeconomic macroeconomic variables such as the growth of Gross Regional Domestik Bruto (GRDP), Human Development Index (HDI), Foreign Investment, Domestic Investment, Regional Income and poverty rates in Indonesia in 2022 in Indonesia. The data used are publication data from the National Innovation Research Agency (BRIN) and the Statistic Indonesia (BPS) in 2022. The analysis model used is the PLS Structural Equation Model (SEM) model with SmartPLS software. The results showed that RCI significantly positively affected HDI, GRDP growth, Domestic Investment, Foreign Investment, and Regional Income. On the other hand, RCI significantly negatively affects the percentage of poor people. A comprehensive and targeted policy is needed so that the Regional Saiang Power Index continues to increase. In addition, supervision is needed related to programs that have been running related to regional competitiveness